2020
DOI: 10.21873/invivo.12013
|View full text |Cite
|
Sign up to set email alerts
|

Serum CEA and CYFRA Levels in ALK-rearranged NSCLC Patients: Correlation With Distant Metastasis

Abstract: Aim: To clarify the correlation between serum levels of carcinoembryonic antigen (CEA) and cytokeratin 19 fragment (CYFRA) and metastasis and survival in anaplastic lymphoma kinase (ALK)-rearranged non-small cell lung cancer (NSCLC) patients. Patients and Methods: CEA and CYFRA levels in 131 ALK-rearranged NSCLC patients were determined using fluorescence in situ hybridization (FISH), real time-reverse transcription polymerase chain reaction, and immunohistochemistry, using biopsy specimens, cytology specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…CEA is also widely used in clinical practice as a serum marker for NSCLC. Recently, Numata et al concluded that elevated serum CEA and CYFRA levels were associated with the presence of bone and liver metastasis and also multiple-organ metastases; however, these high levels were not a powerful indicator of prognosis (38). Furthermore, serum CEA and CYFRA had predictive value with regard to response to therapy in NSCLC, and decreased levels of CYFRA are indicative of objective response (182).…”
Section: Hect and Rld Domain Containing E3 Ubiquitin Protein Ligase 5 (Herc5)mentioning
confidence: 99%
See 1 more Smart Citation
“…CEA is also widely used in clinical practice as a serum marker for NSCLC. Recently, Numata et al concluded that elevated serum CEA and CYFRA levels were associated with the presence of bone and liver metastasis and also multiple-organ metastases; however, these high levels were not a powerful indicator of prognosis (38). Furthermore, serum CEA and CYFRA had predictive value with regard to response to therapy in NSCLC, and decreased levels of CYFRA are indicative of objective response (182).…”
Section: Hect and Rld Domain Containing E3 Ubiquitin Protein Ligase 5 (Herc5)mentioning
confidence: 99%
“…Kong et al. ( 37 ) compared the clinical effect of serum β-type collagen carboxy-terminal peptide and I-CTP in 126 patients, demonstrating that the latter has higher sensitivity and accuracy with a similiar receiver operating characteristic curve [area under the curve ( 38 )] value. Tang et al.…”
Section: Osteocalst- and Bone Resorption-associated Biomarkersmentioning
confidence: 99%
“…In 30% of Stage 1 NSCLC cases, lymph node metastasis is present at the time of diagnosis. Elevated levels of CEA and cytokeratin 19 fragment combination in NSCLC cases may serve as an indicator of liver metastasis and distant organ metastases[ 10 , 50 , 51 ]. In cases where radiological imaging is insufficient and CEA levels are elevated, additional imaging modalities (PET/CT, bronchoscopic ultrasound, and thoracoscopic examinations) may assist in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high level of hemoglobin, might indicating an oxygen-enriched environment which is characterized by having higher nutrient availability and by being rather immunostimulatory, was associated with a more efficient treatment response. (4) CFYRA21-1: serum level of CFYRA21-1 is related to the tumor size, lymph node status, distant Metastasis and the stage of disease 29 , 30 which could assist in predicting immunotherapy efficacy 31 and baseline level was positively correlated with the patient’s risk score before immunotherapy 32 .…”
Section: Discussionmentioning
confidence: 99%